ANAK DIDIK DALAM PERSPEKTIF AL QUR’AN: KAJIAN ANALISIS QS. AT-TAHRIM 66/6, QS AS-SYUARA 26/214, QS. AT-TAUBAH 9/122 DAN QS. AN-NISA 4/170 - Muhammad Rusdi (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
The Alquran has explained how important education is which is very influential in shaping the character of students to become Muslims with noble morals, especially in the development of religious education which is used as the basis for learning both in terms of formal, informal and non-formal institutions which have a very important role in it. This research belongs to the type of literature study research, and then the data is analyzed interactively using a literature review based on the latest references. The results of the research in this discussion show that based on the exposure of the verses of the Alquran, it has explained about the forms of classification regarding students and of course has given the meaning that the most important subjects and objects in education are students, in which they are always prioritized to gain an understanding of learning and character building, and even that cannot be separated from the role of an educator who always directs students to become human beings who are not only intellectual in general knowledge but also intelligent in developing their morals